EMPOWERING EDUCATION: INTEGRATING CRITICAL PEDAGOGY INTO TRANSFORMATIVE TEACHING STRATEGIES - Dwikamayuda, Dewa Made; Ari, Ida Ayu Nyoman Maye Denia; Ekawati, Ni; Nitiasih, Putu Kerti; Riastini, Putu Nanci; Sudatha, I Gde Wawan (Indonesian Journal of Educational Development (IJED), 2024)
The objective of this study is to explore the implications and effectiveness of critical pedagogy in fostering social justice and empowering students in educational settings. This research adopts a qualitative approach, employing literature review to examine the implementation and outcomes of critical pedagogy in various educational contexts The study findings reveal that critical pedagogy serves as a powerful tool for challenging societal norms, empowering marginalized individuals, and promoting social justice within educational settings. Through student-centered learning, collaborative problem-solving, and the development of 21st-century skills, critical pedagogy equips students with the tools and mindset necessary to critically evaluate their surroundings and take action to address oppressive conditions in society. Furthermore, the research highlights the pivotal role of teachers in facilitating critical inquiry, fostering dialogue, and promoting social justice within the classroom. By engaging in self-reflection and transformative practice, educators can create inclusive learning environments that empower students to become active agents in their education and advocates for positive change in society. he contribution of the results of this research to the development of the scientific field lies in providing insights into the practical application of critical pedagogy in classrooms, highlighting its capacity to equip students with critical thinking skills and a sense of agency to address oppressive conditions, thereby advancing the discourse on transformative education practices and social justice within educational contexts.